Tracing the rise of malignant cell lines: Distribution, epidemiology and evolutionary interactions of two transmissible cancers in Tasmanian devils. (28th June 2019) - James, Samantha; Jennings, Geordie; Kwon, Young Mi; Stammnitz, Maximilian; Fraik, Alexandra; Storfer, Andrew; Comte, Sebastien; Pemberton, David; Fox, Samantha; Brown, Bill; Pye, Ruth; Woods, Gregory; et al.
Abstract: Emerging infectious diseases are rising globally and understanding host‐pathogen interactions during the initial stages of disease emergence is essential for assessing potential evolutionary dynamics and designing novel management strategies. Tasmanian devils ( Sarcophilus harrisii ) are endangered due to a transmissible cancer—devil facial tumour disease (DFTD)—that since its emergence in the 1990s, has affected most populations throughout Tasmania. Recent studies suggest that devils are adapting to the DFTD epidemic and that disease‐induced extinction is unlikely. However, in 2014, a second and independently evolved transmissible cancer—devil facial tumour 2 (DFT2)—was discovered at the d'Entrecasteaux peninsula, in south‐east Tasmania, suggesting that the species is prone to transmissible cancers. To date, there is little information about the distribution, epidemiology and effects of DFT2 and its interaction with DFTD. Here, we use data from monitoring surveys and roadkills found within and adjacent to the d'Entrecasteaux peninsula to determine the distribution of both cancers and to compare their epidemiological patterns. Since 2012, a total of 51 DFTD tumours have been confirmed among 26 individuals inside the peninsula and its surroundings, while 40 DFT2 tumours have been confirmed among 23 individuals, and two individuals co‐infected with both tumours. All devils with DFT2 were found within the d'Entrecasteaux peninsula, suggesting that this new transmissible cancer is geographically confined to this area. We found significant differences in tumour bodily location in DFTD and DFT2, with non‐facial tumours more commonly found in DFT2. There was a significant sex bias in DFT2, with most cases reported in males, suggesting that since DFT2 originated from a male host, females might be less susceptible to this cancer. We discuss the implications of our results for understanding the epidemiological and evolutionary interactions of these two contemporary transmissible cancers and evaluating the effectiveness of potential management strategies.